Analisis Warna dan Tekstur pada Menong Purwakarta sebagai Media Komunikasi Budaya - Dewanto, Yahya; Ali, Ferdiansyah; Hasian, Irene (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2023)
Abstract. Menong Purwakarta is one of the local craft products with high artistic and aesthetic value in Indonesia. Menong is not only a handicraft product but also a cultural communication medium that can convey messages about the cultural richness of the archipelago to the community. One of the important elements in Menong Purwakarta is color and texture, which play a crucial role in conveying cultural messages. This research aims to analyze the color and texture in Menong Purwakarta as a cultural communication medium. The method used is qualitative descriptive analysis of the color and texture in Menong Purwakarta, involving direct observation and interviews with Menong craftsmen and local cultural experts. The analysis results show that the use of smart and symbolic colors and textures can enhance the aesthetic appeal of Menong Purwakarta and strengthen the cultural messages conveyed to the community. The implications of these findings contribute significantly to the development of local culture and the preservation of Indonesian cultural heritage.